Rethinking the sacred in religion and nationalism - van der Tol, M; Gorski, P (Taylor & Francis, 2023)
This collection reflects on ways in which right-wing populisms in Europe and the USA unsettle what had become common understandings of the sacred in the study of religion and politics. Whereas secularisation theories long associated the sacred with religion, and in particular Latin Christianity, right-wing populism has demonstrated a remarkable potential for mobilising the sacred through relentless sacralisations of nationhood. Their reliance on Christian imaginaries and symbols for predominantly and possibly exclusively secular purposes means that scholarship must rethink ‘the sacred’ as a potentially immanent phenomenon. Contributions from politics, sociology, and theology discuss the relationship between sacralisations of nationhood and meanings of public space, public policy on migration and integration, and ways in which Christian theology might critique the secular appropriation of religious repertoires.